Olaria de Carvalhal da Louça - Ribeiro, Flávio; Domingues, Ivo (Trabalhos de Antropologia e Etnologia, 2020)
Carvalhal da Louça is a small village of Paranhos da Beira, council of Seia and district of Guarda. The pottery industry here started in the XVIII century and soon became the main source of economy, as it can be seen through its toponymy. The tasks involved with the manufacture of goods were shared by the potter and his wife, which influenced the former to follow a sort of matrimonial strategy. TheJ objects produced were ali for domestic and utilitarian function. Its commercialization was done within a radius of 50 km and every piece had to be carried on the head of the distributor. However, since this manufacturing activity did not bring in a great income, the potters turned to agricultura! interests as means of survival. Pottery making in Carvalhal da Louça started to decline in the middle of this century for various reasons: competition caused by the arising of plastic materiais, the absence of potters due to emigration and the lack of interest shown by the new generations towards this activity. As a result, pottery making in Carvalhal da Louça is today almost extinct.